Energy Efficiency in OIC Countries: SDG 7 Output - Rusydiana, Aam S.; Laila, Nisful; Tubastuvi, Naelati; Ibrahim, Mohamad Andri; Marlina, Lina (International Journal of Energy Economics and Policy, 2020)
Over the past few decades, countries in the Association of Islamic Cooperation Organizations (OIC) have reached various levels of economic development. At present, increasing energy access is one of the goals to be achieved by ensuring affordable, reliable, sustainable and modern energy access. This study aims to measure the effectiveness of energy access based on the indicators of the seventh sustainable developmet goals (SDGs) in 50 countries that are members of the OIC during the period 2010-2017. Efficiency measurements are carried out using the Data Envelopment Analysis (DEA) method. The productivity measurement is done by using the Malmquist Productivity Index (MPI). The results showed that Yemen was the country that had the highest rate of increase with a TFP value of 1.194. While the State of Egypt was the country that experienced the largest decline with a TFP value of 0.821. On the other hand, there are differences in the level of efficiency regionally, where Muslim countries in the European continent are then followed by the countries of the West Asian region in the second position and the third position is the central African region which is superior to the region Other Africa. Keywords: Sustainable Developmet Goals, Data Envelopment Analysis, Efficiency, Energy Access, Islamic Cooperation Organizations JEL Classifications: O1, 05, Q4 DOI: https://doi.org/10.32479/ijeep.10499